Observations of Astiericeras astierianum (d'Orbigny, 1842) ( Cretaceous Ammonoidea). - Kennedy, W (1986)
Astiericeras astierianum (d'Orbigny, 1842) is redescribed, the type material illustrated for the first time and the range of intraspecific variation and striking sexual dimorphism documented. Previous suggestions that the early ontogeny of Astiericeras supports derivation from Douvilleiceras de Grossouvre, 1894 of the Douvilleiceratinae are in error: the genus and species are distinctive at the earliest diameters seen and ornament gives no clue to affinities. The sutural formula is that characteristic of some Douvilleicerataceae, however, to which superfamily the species is assigned, as the only member of the family Astiericeratidae Bresitroffer, 1953. It is thus a scaphitoid hetermorph, derived from normally coiled immediate ancestors that are themselves recoiled derivatives of an original heteromorphic stock.-Author